Cytotoxic activity of coumarins from Micromelum minutum - Susidarti, Ratna Asmah; Rahmani, Mawardi; Mohd Ismail, Hazar Bebe; Md. Sukari, Mohd Aspollah; Yap, Taufiq Yun Hin; Ee, Gwendoline Cheng Lian; Ali, Abdul Manaf (Informa Healthcare, 2009)
The crude petroleum ether and chloroform extracts of Micromelum minutum (G. Frost.) Wright & Arn (Rutaceae) showed strong cytotoxic activity when tested against a T-lymphoblastic leukemia cell line. Further fractionation of the extracts resulted in the isolation of five new coumarins 3″,4″-dihydrocapnolactone, 2′,3′-epoxyisocapnolactone, 8-hydroxyisocapnolactone-29,39-diol, 8-hydroxy-3″,4″- dihydrocapnolactone-29,39-diol and 8,4″-dihydroxy-3″,4″- dihydrocapnolactone-29,39-diol, and two triterpenes. Some of these compounds were strongly active against T-lymphoblastic leukemia (CEM-SS), promyeolocytic leukemia (HL60), cervical cancer (HeLa) and liver cancer (HepG2) cell lines. 8-Hydroxyisocapnolactone-29,39-diol was found to be the most active with IC50 values of 2.9, 2.5, 6.9, and 5.9 μg/ml, respectively. This was followed by 2′,3′-epoxyisocapnolactone. When evaluated against the normal mouse fibroblast (3T3) cell line, 8-hydroxyisocapnolactone-29,39-diol was found to be inactive, hence it could serve as a valuable lead for further design and synthesis of more active analogues.